Development of Sn–Cu–Sb alloys for making lead- and bismuth-free pewter - Wong, Y.H.; Ramesh, S.; Tan, C.Y.; Projjal, B. (Carl Hanser Verlag, 2014)
A systematic study on the development of a set of Sn–Cu–Sb alloys and their characteristics, such as phases evolved, mechanical properties, physical properties, and microstructures, that are commonly sought for making pewter is presented. Alloys with various nominal compositions of Sn–Cu (1–3%)–Sb (3–6%) were prepared and they were die cast for complete characterization. The samples were characterized for hardness, malleability, density, microstructure, and phase identification. The study is expected to help in selecting the right composition of the alloys for making pewter with appropriate combination of properties.